Appointment reminders to increase uptake of HIV retesting by at‐risk individuals: a randomized controlled study in Thailand. Issue 4 (15th April 2020) - Salvadori, Nicolas; Adam, Pierrick; Mary, Jean‐Yves; Decker, Luc; Sabin, Lucie; Chevret, Sylvie; Arunothong, Surachet; Khamduang, Woottichai; Luangsook, Prapan; Suksa‐ardphasu, Visitsak; Achalapong, Jullapong; Rouzioux, Christine; et al.
Abstract: Introduction: Frequent HIV testing of at‐risk individuals is crucial to detect and treat infections early and prevent transmissions. We assessed the effect of reminders on HIV retesting uptake. Methods: The study was conducted within a programme involving four facilities providing free‐of‐charge HIV, syphilis and hepatitis B and C testing and counselling in northern Thailand. Individuals found HIV negative and identified at risk by counsellors were invited to participate in a three‐arm, open‐label, randomized, controlled trial comparing: (a) "No Appointment & No Reminder" (control arm); (b) "No Appointment but Reminder": short message service (SMS) sent 24 weeks after the enrolment visit to remind booking an appointment, and sent again one week later if no appointment was booked; and (c) "Appointment & Reminder": appointment scheduled during the enrolment visit and SMS sent one week before appointment to ask for confirmation; if no response: single call made within one business day. The primary endpoint was a HIV retest within seven months after the enrolment visit. The cost of each reminder strategy was calculated as the sum of the following costs in United States dollars (USD): time spent by participants, counsellors and hotline staff; phone calls made; and SMS sent. The target sample size was 217 participants per arm (651 overall). Results: Between April and November 2017, 651 participants were randomized. The proportion presenting for HIV retesting within seven months was 11.2% (24/215) in the control arm, versus 19.3% (42/218) in "No Appointment but Reminder" ( p  = 0.023) and 36.7% (80/218) in "Appointment & Reminder" ( p  < 0.001). Differences in proportions compared to the control arm were respectively +8.1% (95% CI: +1.4% to +14.8%) and +25.5% (+17.9% to +33.2%). The incremental cost‐effectiveness ratios of "No Appointment but Reminder" and "Appointment & Reminder" compared to the control arm were respectively USD 0.05 and USD 0.14 per participant for each 5% increase in HIV retesting uptake within seven months. Conclusions: Scheduling an appointment and sending a reminder one week before was a simple, easy‐to‐implement and affordable intervention that significantly increased HIV retesting uptake in these at‐risk individuals. The personal phone call to clients probably contributed, and also improved service efficiency.